2004
DOI: 10.1891/vivi.19.6.689.66342
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Overt and Relational Aggression and Psychosocial Adjustment in Undergraduate College Students

Abstract: This study examined the relations between overt and relational aggression, social anxiety, loneliness, depressive symptoms, and alcohol and drug use in a sample of 287 undergraduate college students. Consistent with prior work, men reported engaging in more overt aggression than women. Contrary to our predictions, men also reported engaging in more relational aggression than women. Results also indicated that overt and relational aggression were positively associated with social anxiety, loneliness, depressive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
65
2
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(76 citation statements)
references
References 36 publications
7
65
2
2
Order By: Relevance
“…Based on the preceding literature review, there do appear to be unique relationships between anxiety and the different forms, functions, and subtypes of aggression. Specifically, anxiety seems to co-occur more frequently with relational aggression (Crick 1995;Storch et al 2004), reactive aggression (Fite et al 2010), and reactive relational aggression (Marsee et al 2008). Further, conceptualizing anxiety and aggression as components of the larger fight/flight system emphasizes the importance of the often interconnected nature of these behaviors and suggests that they are dictated by the same underlying emotional and cognitive mechanisms.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on the preceding literature review, there do appear to be unique relationships between anxiety and the different forms, functions, and subtypes of aggression. Specifically, anxiety seems to co-occur more frequently with relational aggression (Crick 1995;Storch et al 2004), reactive aggression (Fite et al 2010), and reactive relational aggression (Marsee et al 2008). Further, conceptualizing anxiety and aggression as components of the larger fight/flight system emphasizes the importance of the often interconnected nature of these behaviors and suggests that they are dictated by the same underlying emotional and cognitive mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Taken together, the preliminary research on the co-occurrence of anxiety and aggression described in the preceding paragraphs suggest that there may in fact be differing relationships between internalizing symptoms of anxiety and externalizing symptoms of these specific types of aggression such that anxiety seems to co-occur more frequently with relational aggression (Crick 1995;Storch et al 2004), reactive aggression (Fite et al 2010), and reactive relational aggression (Marsee et al 2008). Reasoning follows that considering the presence or absence of anxious behavior may aid in determining the specific type of aggression present in clinical settings which will be useful in aiding treatment planning.…”
mentioning
confidence: 94%
See 1 more Smart Citation
“…Bagner and colleagues (2007) found a similar pattern of results related to romantic relational aggression, wherein high levels were correlated with social anxiety, loneliness, and depressive symptoms. In terms of gender differences, Storch et al (2004) found that social aggression was significantly correlated with social anxiety, loneliness, and depression among women. Finally, Werner and Crick (1999) also reported a link between peer-nominated social aggression and bulimia symptoms in women.…”
Section: Individual-level Findingsmentioning
confidence: 99%
“…Relational Aggression, Depressive Symptoms, and Suicidal Ideation Specific to internalizing symptoms, relational aggression has been found to be associated with depressive symptoms, low self-esteem, and loneliness [1,5,[9][10][11]. For example, in a community sample of third through sixth grade children, relationally aggressive children reported higher levels of depression than those who were not classified as relationally aggressive.…”
Section: Relational Aggressionmentioning
confidence: 99%